Selection of self-priming molecular replicators - Park, Daechan; Ellington, Andrew D.; Jung, Cheulhee (Nucleic Acids Research, 2019)
Self-priming amplification of oligonucleotides is possible based on foldback of 3 ends, self-priming, and concatemerization, especially in the presence of phosphorothioate linkages. Such a simple replicative mechanism may have led to the accumulation of specific replicators at or near the origin of life. To determine how early replicators may have competed with one another, we have carried out selections with phosphorothiolated hairpins appended to a short random sequence library (N10). Upon the addition of deoxynucleoside triphosphates and a polymerase, concatemers quickly formed, and those random sequences that templated the insertion of purines, especially during initiation, quickly predominated. Over several serial transfers, particular sequences accumulated, and in isolation these were shown to out-compete less efficient replicators.
Keywords: Base Sequence; Consensus Sequence; DNA Primers; DNA Replication; DNA, Concatenated; Evolution, Molecular; Oligonucleotides; Origin of Life; Templates, Genetic